Acceptance Analysis of a Learner Experience Evaluation Model - Santos, Gabriela Corbari dos; Silva, Deivid Eive dos S.; Peres, Letícia Mara; Valentim, Natasha M. C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.241385, 2024)
Learner eXperience (LX) is defined as the perceptions, answers, and performances of learners interacting with learning environments, educational products, and resources. Thus, we proposed a model to assess and support the improvement of the learner? 's experience using Digital Information and Communication Technologies (DICTs) during learning, called [anonymous]. This paper presents the acceptance analysis of the [anonymous] and its evolution with twelve learners and one higher education teacher. The acceptance evaluation carried out in this study is important because it helps to improve and verify the contribution of the [anonymous] model, based on the perception of learners and teacher, who are the stakeholders in the educational process.